Sustainable Chemical Engineering: The Synergy of Science and Islamic Values in Occupational Health and Safety (K3) and Natural Resource Management - Nadya Noor Firdaus; Amelia Nurwulan; Mohammad Faris Feriansyah; Mokh. Iman Firmansyah; Anurag Hazarika (Yayasan Azhar Amanaa Yogyakarta, 2026)
The development of chemical technology and industry has led to the emergence of a new paradigm in natural resource management (SDA), which demands a balance between economic interests, environmental sustainability, and occupational safety. In this context, chemical engineering plays a crucial role in designing sustainable processes that are energy efficient and low in waste, while the implementation of Occupational Safety and Health (K3) ensures the prevention of workplace accidents and maintains the continuity of industrial operations. However, sustainability is not only determined by technical aspects, but also by moral and spiritual values. Islamic teachings, through the concepts of khalīfah, mīzān, amanah, and the prohibition of fasād, emphasize that humans have a significant responsibility to maintain the balance of nature, as we live side by side with the environment. Nature provides us with air, water, food, and everything else we need to survive. Thus, the synergy between the principles of sustainable chemical engineering, K3 regulations, and Islamic values forms the foundation for fair, safe, and responsible natural resource management. This research uses a qualitative approach by reviewing various literature, such as journals, books, and previous research results related to the integration of these three aspects. The study results indicate that the simultaneous application of Islamic scientific and ethical principles can strengthen efficient, safe, and environmentally friendly chemical industry practices, and has the potential to become a basis for policy development, education, and implementation of sustainable industry in Indonesia.